Episciences overlay journals: A bridge between scientific publications, open repositories, data and software repositories - Tournoy, Raphaël (Septentrio Conference Series, 2023)
Watch VIDEO.Episciences is a publishing platform for diamond open access overlay journals. The ambition is to provide scientific communities with the technical means to produce high-quality, cost-effective journals in line with FAIR principles. The process is based on open repositories (arXiv; Zenodo; HAL). All the published content of a journal is hosted on repositories. Episciences is therefore set up as a service layer for repositories, using them as input and output for open access publication. The platform was launched in 2013 as a peer review service for preprints hosted in open archives. Over the years, the list of services offered has grown and adapted to new trends in scientific publications. For example, peer review reports are now a new type of content that can be hosted in repositories, along with datasets and software code for publications. Support for these new objects in Episciences increases transparency and reproducibility of science. Support for datasets and software code also means that both data journals and software journals can be easily created on top of repositories.The platform has implemented new protocols and workflows promoted by the Confederation of Open Access Repositories (COAR) Next Generation Working Group, such as COAR Notify and SignPosting. It has enabled us to build innovative new services for researchers on top of the HAL repository. We have also connected Episciences to other open science services such as OpenAIRE Graph, OpenCitations and Scholexplorer. This has allowed us to add new services at the same time for journals and the HAL repository. The presentation will explain how Episciences and overlay journals in general can be a bridge between publications, open repositories, data and software repositories - and more broadly with open science infrastructures.
Keywords: Overlay journals; Next generation repositories; Overlay services